Active Vibration Isolation of a Maglev Inertially Stabilized Platform Based on an Improved Linear Extended State Observer - Shi, Wanfa; Liu, Kun; Zhao, Wenpeng (IEEE access, 2021)
An inertially stabilized platform is subject to the vibration force and moment from its support base, and low-frequency vibrations cannot be eliminated by mechanical vibration isolation. Combining gimbals with magnetic bearings instead of mechanical bearings, a maglev inertially stabilized platform (MISP) is characterized by no friction or an active vibration control capability. In this paper, an improved linear extended state observer (LESO) replacing displacement error with next-order error is proposed to estimate the low-frequency vibration and improve the estimation accuracy. An active vibration isolation control method is then designed to realize cancellation compensation on the MISP. Finally, a simulation example is presented to validate that the proposed measures can effectively eliminate the low-frequency vibration force transmitted from the base and ensure the stability of the MISP.